Pentingnya Pendidikan Karakter Dalam Pembentukan Moral Anak Sekolah Dasar - Lestari, Kinanti Anisa; Julia, Ajeng; Putri, Nanda Aditya; Darusalam, Muhammad Rizki; Caturiasari, Jennyta; Wahyudin, Dede (JURNAL SINEKTIK, 2024)
The purpose of this research is to find out the character of elementary school-age children, and character education for elementary school children, as well as the role of teachers and parents in building children's character. This research uses a type of qualitative research using the method of literature study or literature study. Subjects in the study were taken from various previous studies that had similarities or relevance to this research. The results of this study indicate that character education has a significant role in the moral formation of children at elementary school age, this role must be supported and assisted by teachers and parents as the main actors in the formation of good character and morals of children. Education and instilling good character and morals in elementary school-age children can be carried out by carrying out learning that has positive values, developing social skills, and instilling an understanding of the consequences of every action taken by children at elementary school age.